Analisis efek ukuran perusahaan, profitabilitas, likuditas, dan kinerja lingkungan terhadap pengungkapan Islamic Social Reporting - Muhammad Rusydi Aziz; Roekhudin Roekhudin; Wuryan Andayani (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2019)
This study aims to test and empirically prove the influence of company size, profitability, liquidity and environmental performance on the disclosure of Islamic Social Reporting. This type of research is quantitative research, uses secondary data taken from the Indonesia Stock Exchange (IDX) or the Ministry of Environment. Based on the purposive sampling method, there are 33 samples of companies for 3 years in companies registered with ISSI. This study uses a special regression analysis for panel data using Eviews 10. The results of this study indicate that company size and profitability have a positive effect on the disclosure of Islamic Social Reporting. While liquidity and environmental performance failed to have an effect on the disclosure of Islamic Social Reporting. The results of this study are expected to be a consideration of what factors influence the disclosure of Islamic Social Reporting on companies listed on the Indonesian Islamic stock index (ISSI) in 2015 - 2017 which are also listed on PROPER